Overlapping and segregated changes of functional hubs in melancholic depression and non-melancholic depression. (October 2022) - Fu, Xiaoya; Yang, Xiaolun; Cui, Xilong; Liu, Feng; Li, Huabing; Yan, Meiqi; Xie, Guangrong; Guo, Wenbin
Abstract: Background: Previous research found associations between neuropsychiatric disorders and patterns of highly connected "hub" nodes, which are crucial in coordinating brain functions. Melancholic depression is considered a relatively distinct and homogenous subtype of major depressive disorder (MDD), which responds better to pharmacological treatments than placebos or psychotherapies. Accordingly, melancholic depression probably has distinct neuropathological underpinnings. This study aims to examine the overlapping and segregated changes of functional hubs in melancholic and non-melancholic MDD. Methods: Thirty-one melancholic patients, 28 non-melancholic patients, and 32 healthy controls were included. Resting-state functional imaging data were analyzed using global functional connectivity. Results: Both melancholic and non-melancholic patients had increased GFC in the bilateral insula and decreased GFC in the PCC/precuneus compared to HCs. The distinction was that melancholic patients showed increased GFC in the bilateral thalamus, right inferior parietal lobule (IPL), and left cerebellum Crus I and decreased GFC in the left temporal lobe, whereas non-melancholic patients showed increased GFC in the left superior parietal lobe. Additionally, compared with non-melancholic patients, melancholic individuals displayed significant increases of GFC in the left IPL and cerebellum. Conclusion: Increased GFC of the insula and decreased GFC of the PCC and precuneus are the common abnormalities of melancholic and non-melancholic MDD. Hyperconnectivity of the IPL and cerebellum might be distinctive neuropathological features of melancholic MDD.